The Importance of Surface Orientation in Biodiversity Monitoring Protocols: The Case of Patagonian Rocky Reefs - Bravo, Gonzalo; Livore, Juan Pablo; Bigatti, Gregorio (Frontiers in Marine Science, 2020)
Temperate rocky reefs in Atlantic Patagonia are productive areas that support a high diversity of invertebrates, algae, and fishes. Complex surface structures on rocky reefs offer a range of microhabitats, which in turn, lead to a broad variety of co-existing species. Despite their ecological importance and the ecosystem services they provide, Patagonian rocky reef habitats have received limited attention. Until now studies have not discerned nor consequently described the assemblages found on each of the different surface orientations, namely horizontal, vertical, overhang and cavefloor. During this study we developed a protocol for sampling different surface orientations on subtidal rocky reefs using georeferenced high-resolution photoquadrats. We described and compared the epibenthic assemblage of surface orientations on 7 rocky reefs within 1–25 m depth in a northern Patagonia gulf. A total of 70 taxa were identified (12 macroalgae, 44 invertebrates, 10 tunicates, and 4 fishes), which doubles the number of species previously reported for the area. Each surface orientation presented a different assemblage structure while species richness was higher on vertical surfaces. The overhang surfaces had the most distinct assemblage conformed by cnidarians, tunicates, sponges and the absence of algae. The average overall species richness increased with depth due to the increase of sponge and tunicate species. Our results highlight the need of including several surface orientations in rocky reef biodiversity monitoring. This study offers a protocol for large-scale programs aimed at monitoring changes in biodiversity, which is broadly accessible and will provide accurate information. With robust yet simple, non-destructive and relatively low-cost practices this protocol can adequately assess changes in marine habitats, which provide important ecosystem services.